Spesifikasi Pola Dermatoglifi Penderita Retardasi Mental Pada Siswa SLB YPAC Palembang - Robiatun, Robiatun; Kustiati, Rita (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2021)
Mental retardation a condition of having mental developmental delay and below avreage intellectual ability which is less than an Intelligence Quotient (IQ) of 70. This intelectual disability is not a disease, but as the result of several kind of other diseases, trauma, infection, and problems during pregnancy such as malnutrition, drugs consumption, toxic, and genetic diseases. Dermatoglyphic patterns analysis can be used as an alternative diagnostic tool to see the possibility of having mental retardation at earlier age by analyzing dermatoglyphic patterns which is typical of each person. The objective of this research was to learn more about specific dermatoglyphic patterns of mental retardation patients. The method of research applied in this study was observational research with Cross-Sectional Study research design. Fiftyeight persons were involved in this research, which consisted of 33 mental retardation patients and 25 non-retarded persons in SLB YPAC Palembang. Analysis was done by analyzing configuration of dermatoglyphic patterns, TTC, TRC, and ATD angle. This research resulted in the finding of major dermatoglyphic pattern found in mental retardation patients which was Loop pattern. There was a significant difference Arch patterns with the value of p = 0.03. No difference found in Triradius Ridge Count (TRC), Total Triradius Count (TTC), and right ATD angle with the value of P = 0.451. But there was a difference found in left ATD angle with the value of P = 0.005. From this research, it was concluded that there was no specific dermatoglyphic pattern found in students with mental retardation in SLB YPAC Palembang which was proved by the value of P > 0.05. AbstrakRetardasi Mental suatu keadaan keterlambatan dalam perkembangan dan memiliki kemampuan intelektual dibawah normal, yaitu Intelligence Question (IQ) di bawah 70. Kelainan intelektual ini bukanlah merupakan suatu penyakit tetapi merupakan akibat dari berbagai penyakit lain, trauma, infeksi, masalah dalam kehamilan seperti kurang nutrisi, obat-obatan, racun dan juga penyakit genetik. Pola dermatoglifi dapat digunakan sebagai alternative untuk melihat kemungkinan retardasi mental pada diri seseorang sejak dini pada kekhasan pola dermatoglifi setiap orang. Penelitian ini bertujuan untuk mengetahui bagaimana spesifikasi pola dermatoglifi pada penderita retadasi mental. Penelitian ini merupakan observasional dengan rancangan penelitian Cross Sectional Study. Melibatkan 58 responden yang terdiri dari 33 resonden penderita retardasi mental, dan 25 responden non retardasi mental sisa SLB YPAC Palembang. Dengan melihat pola dermatiglifi, TTC, TRC, dan sudut ATD. Hasil penelitian ini didapatkan bahwa pola dermatoglifi pada penderita retadasi mental ditemukan paling banyak adalah pola Loop, ada perbedaan bermakna pola dermatoglifi Arch dengan nilai p = 0,03, tidak ada perbedaan Triradius Ridge Count (TRC) dan Total Triradius Count (TTC). Tidak ada perbedaan sudut ATD kanan dengan nilai p = 0,451 serta ada perbedaan sudut ATD kiri dengan nilai p = 0,005. Dari penelitian ini disimpulkan tidak ada spesifikasi pola dermatoglifi penderita retardasi mental pada siswa SLB YPAC Palembang, dengan nilai (p>0,05).